Green Organizational Culture, Corporate Social Responsibility Implementation, and Food Safety - Liu, Xiao; Lin, Kuen-Lin (Frontiers in Psychology, 2020)
Food safety, ultimately, is a human-centred work. No matter how regulations are coercively released and implemented, the free will and behaviors of human actors (e.g., employees) leads to a real result in food safety. A real motivator of such free will and behaviors is organizational culture that stimulates meaningful organizational actions. Based on such rationale, this conceptual paper with Walmart as an example case sets to discuss the relationships between green organizational culture, corporate social responsibility, and food safety. As organizational culture has been largely discussed in Management and Business literature, green organizational culture and its impacts on socially and environmentally friendly organizational behaviors, as well as public health outcomes like food safety, is wanted. With the clarification of the relationships between these three important constructs, theoretical implications for future research and practical implications for governance and policy-making are well generated.